Nebenwirkungsmanagement in der Immunonkologie - Reinmuth, Niels; Bitzer, Michael; Deschler-Baier, Barbara; Fischer, Jürgen; Kuon, Jonas; Leipe, Jan; Rawluk, Justyna; Schulz, Christian; Heußel, Claus Peter; Schultheiß, Michael (Deutsche medizinische Wochenschrift, 2019)
The immune oncological treatment approach uses immune checkpoint inhibitors to prevent tumor cells from shutting down the immune system, and thus from escaping immune response. Following the clinical success of immune checkpoint inhibitors, the number of approved immune oncological therapies continues to increase. Response rates and overall survival with anti-PD-1/PD-L1 and CTLA-4 blockade could be further improved by combining both treatment approaches. However, checkpoint inhibition is associated with a unique spectrum of side effects termed immune-related adverse events. These typically occur 3 to 6 months after treatment start and resolve with adequate management procedures if detected early on. Therefore, profound patient education, sensitizing and monitoring are mandatory. We describe in this article selected frequent and rare adverse events that are clinically relevant. Furthermore, using case reports, interdisciplinary experts share their practice-based experience in the management of frequent pneumonic, endocrine, and gastro-intestinal immune-related adverse events.
Gesehen am 09.05.2019